Titanium diboride composite with improved sintering characteristics. (March 2015) - Chao, Sheng; Goldsmith, Jason; Banerjee, Dev
Abstract: Titanium diboride (TiB2 ) and its ceramic composites were prepared by hot pressing process. The sintering process, phase evolution, microstructure and mechanical properties of TiB2 ceramics prepared by using different milling media materials: tungsten carbide (WC/Co) or SiAlON was studied. It was found that the inclusion of WC/Co significantly improved the sinterability of the TiB2 ceramics. A core/rim structure with pure TiB2 as the core and W-rich TiB2, i.e. (Ti, W)B2 as the rim was identified. Microstructure analysis revealed that this core/rim structure was formed through a dissolution and re-precipitation process. In addition, silicon carbide (SiC) was also introduced to form TiB2 –SiC composites. The addition of SiC as the secondary phase not only improved the sinterability but also led to greatly enhanced fracture toughness. The optimum mechanical properties with Vickers hardness 22 GPa, and fracture toughness 6 MPa m 1/2 were obtained on TiB2 –SiC composites milled with WC/Co. Highlights: The sinterability of TiB2 was greatly improved by WC/Co inclusion. A core (TiB2 )/rim ((Ti, W)B2 ) structure formed through a dissolution and reprecipitation process. Significantly improved fracture toughness was obtained on TiB2 -SiC composites.